The Effect Of Isometric Handgrip Exercise And Watermelon Juice On Reducing Blood Pressure In Hypertension Sufferers In The RT 07 RW 06 Pengasinan Sawangan Depok Area - Azmilia, Ulfah; Setiawan, Rian Agus; Oktavia, Alfonsa Reni (Jurnal EduHealth, 2024)
Hypertension is often called the silent killer because it generally has no signs and symptoms, so it is only discovered after it causes complications. One non-pharmacological therapy that can be given to reduce blood pressure in hypertensive patients is a combination of isometric handgrip exercise therapy and watermelon juice. This study aims to determine the effect of isometric handgrip exercise and watermelon juice on reducing blood pressure in hypertension sufferers. This research design uses a quasi-experiment with a pre-post-test research design without control. The population in this study was 45 people, with a sample size of 18 people. The results of this study show that there is an effect of isometric handgrip exercise and watermelon juice on reducing blood pressure in hypertension sufferers in the RT 07 RW 06 Pengasinan Sawangan Depok area with a p-value of 0.000 (p<0.05) on systolic blood pressure and a p-value of 0.000 (p< 0.000) in diastolic blood pressure. It is hoped that the results of this research can be used as an alternative treatment to lower blood pressure in hypertension sufferers and can add information that the treatment of hypertension is not only with medication but can be supplemented with non-pharmacological therapy such as watermelon juice, and isometric handgrip exercise intervention can be an alternative patient activity that has an effect. Stable blood pressure can be maintained independently at home.